The Prevalence and Correlation of Foot Deformity in Primary Osteoarthritis of the Knee - Jha, Daman; Unprasert, Prangthong; Chuckpaiwong, Bavornrit (Journal of Southeast Asian Orthopaedics, 2021)
Background: Foot deformities have long been recognized as highly prevalent in older people. Knee osteoarthritis (OA) is a common painful and chronic condition that affects a large proportion of older people. The presence of foot deformities increase disability levels in knee osteoarthritis. The purpose of our study is to investigate the prevalence and correlation of foot deformity in primary knee OA. Methods: The study design was a cross-sectional survey study of the primary OA knee patients during 4 years period presented in the IPD and OPD patient in Siriraj Orthopedic Department. 113 patients were enrolled in the study. The measure for the association was between the femur-tibia angle (FTA), the hallux valgus angle (HVA), the intermetatarsal angle (IMA), and the calcaneal pitch angle. Results: The prevalence of foot deformities in primary OA knee patients was 70.5% (n=80). The prevalence of the hallux valgus, pes planus and hind foot varus in primary OA knee patients were 51.9%, 41.8%, and 32.9%. The radiographic measurements have no statistically significant association between the alignment of osteoarthritis of the knee (the femur-tibia angle) and foot deformities. No significant association was seen between the femur-tibia angle (FTA), the hallux valgus angle (HVA), the intermetatarsal angle (IMA), and the calcaneal pitch. Conclusions: The prevalence of foot deformities is significantly higher in OA knee. Hallux valgus, pes planus and hind foot varus were the most common foot deformity associated with OA knee.